2012
DOI: 10.1016/j.pbb.2011.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Food restriction increases acquisition, persistence and drug prime-induced expression of a cocaine-conditioned place preference in rats

Abstract: Cocaine conditioned place preference (CPP) is more persistent in food-restricted than ad libitum fed rats. This study assessed whether food restriction acts during conditioning and/or expression to increase persistence. In Experiment 1, rats were food-restricted during conditioning with a 7.0 mg/kg (i.p.) dose of cocaine. After the first CPP test, half of the rats were switched to ad libitum feeding for three weeks, half remained on food restriction, and this was followed by CPP testing. Rats tested under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 58 publications
5
32
1
Order By: Relevance
“…Functional MRI studies using disorder-relevant stimuli such as high calorie foods and distorted body images induce elevated amygdala reactivity in subjects with AN relative to healthy controls (Ellison et al, 1998;Joos et al, 2011); positron emission tomography studies show hypoperfusion of structures associated with fear extinction-namely the medial prefrontal cortex-and hyperperfusion of the amygdala À hippocampal complex in AN (Takano et al, 2001). Consistent with this clinical perspective, our results suggest that CR may normalize dysregulated fear responses in AN, which in combination with trait or acquired alterations in cortico-striatal circuit function that have been described in AN, may help explain why dieting behavior is so vigorously reinforced as well as the high comorbidity of anorexia with obsessive-compulsive disorder (Milad and Rauch, 2012;Wagner et al, 2007;Zheng et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…Functional MRI studies using disorder-relevant stimuli such as high calorie foods and distorted body images induce elevated amygdala reactivity in subjects with AN relative to healthy controls (Ellison et al, 1998;Joos et al, 2011); positron emission tomography studies show hypoperfusion of structures associated with fear extinction-namely the medial prefrontal cortex-and hyperperfusion of the amygdala À hippocampal complex in AN (Takano et al, 2001). Consistent with this clinical perspective, our results suggest that CR may normalize dysregulated fear responses in AN, which in combination with trait or acquired alterations in cortico-striatal circuit function that have been described in AN, may help explain why dieting behavior is so vigorously reinforced as well as the high comorbidity of anorexia with obsessive-compulsive disorder (Milad and Rauch, 2012;Wagner et al, 2007;Zheng et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, one-third of callers to the National Cocaine Hotline who met criteria for cocaine abuse also met criteria for bulimia and/or anorexia nervosa (Jonas and Gold 1987). Using a CPP paradigm, it was previously observed that FR in rats increases the incentive effect of a cocaine-paired environment in much the same way that it increases the rewarding effect of cocaine itself (Liu et al 2011; Zheng et al 2012; Zheng et al 2013). This observation suggested that FR may not only increase vulnerability to initial drug use by enhancing reward magnitude but may increase relapse risk by enhancing the incentive effect of contexts associated with the subjective effects of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…This well-established effect is due, at least in part, to increased drug reward magnitude which has been attributed to increased D1 dopamine (DA) receptor signaling and calcium-permeable AMPA receptors (CP-AMPARs) in nucleus accumbens (NAc) shell (Cabeza de Vaca and Carr 1998; Carr et al 2003; Carr et al 2010). From a clinical standpoint, an equally if not more hazardous effect of food restriction (FR) is the enhanced behavioral responsiveness to a drug-paired context, as demonstrated in cocaine conditioned place preference (CPP) studies (Liu et al 2011; Zheng et al 2012; Zheng et al 2013). Context-induced craving is a common relapse trigger in addicts (Childress et al 1993; See 2002), and it may be presumed that the hyperphagia and body weight gain that accompany psychostimulant abstinence sometimes provoke weight loss dieting (Orsini et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a substantial body of work by Carr et al (49, 50) has established that weight loss enhances the rewarding effects of drugs of abuse and up-regulates mechanisms of synaptic plasticity in the nucleus accumbens. These findings suggest a mechanistic basis for the development of particularly well-entrenched habits, such as resistance of cocaine-conditioned behavior to extinction in food-restricted rodents (51). …”
Section: The Dieting Behavior Becomes Habitualmentioning
confidence: 94%